Attività laboratoriali del PLS Chimica: un’opportunità per insegnanti e studenti - Funicello, Maria (Chimica nella Scuola, 2025)
For many years now, PLS has offered teachers and students, in the three-year period of secondary school, the opportunity to practically try their hand at various chemistry topics. The aim that has accompanied these activities since its inception is both to bring out scientific vocations in students (in our case particularly in the chemical field) and to contribute to the training of science teachers with new teaching proposals. The common thread in the PLS Chemistry activities of the current academic year was “The colors of chemistry” and was divided into three laboratory activities which involved different disciplines present on site. In this communication, the educational ideas offered as part of the project and the students’ response will be discussed.